Influence of Polysaccharide Krestin from Coriolus versicolor Extract on Nitrite and Malondialdehyde Concencentrations of Mus musculus Serum Exposed by Mycobacterium tuberculosis - Wahyuningsih, Sri Puji Astuti; Pramudya, Manikya; Sugiharto, Sugiharto (Biosaintifika: Journal of Biology & Biology Education, 2016)
Mycobacterium tuberculosis is a major infection agent of tuberculosis that is controlled by the response of cell-mediated immunity. It is macrophages and cytolytic T lymphocytes. Activated macrophages will produce free radicals. Excessive free radicals cause tissue damage. Polysaccharide krestin contains ?-glucan. It is a scavenger of free radicals. This research aimed to identify the influence of polysaccharide krestin from C. versicolor on nitrite and malondialdehyde concentrations of mice serum exposed by M. tuberculosis. Nitrite concentration was determined by nitrite assay. Malondialdehyde concentration was determined by TBARS assay. The result showed that adding polysaccharide krestin before exposure (P1) and adding polysaccharide krestin before-after exposure (P3) had the best potential to decrease nitrite concentration. Nitrite concentrations of P1 and P3 were 1.364 0.523 M and 1.456 0.712 M respectively. Meanwhile, P1 group and adding polysaccharide krestin after exposure (P2) had the best potential to decrease malondialdehyde concentration. Malondialdehyde concentrations of P1 and P2 were 1125.86 97.96 M and 953.86 328.16 M respectively. Their nitrite and malondialdehyde concentrations decreased, compared to K and K- groups. The research conclusion was that adding polysaccharide krestin before exposure could decrease both nitrite and malondialdehyde concentrations.How to CiteWahyuningsih, S., Pramudya, M., & Sugiharto, S. (2016). Influence of Polysaccharide Krestin from Coriolus versicolor Extract on Nitrite and Malondialdehyde Concencentrations of Mus musculus Serum Exposed by Mycobacterium tuberculosis. Biosaintifika: Journal of Biology & Biology Education, 8(1), 12-17.